The efficacy of fortified human milk compared to human milk alone for the growth of low birth weight infants - Dewi Kumara Wati Ketut; Soetjiningsih Soetjiningsih; Suandi IKG; Hamid H A (Paediatrica Indonesiana, 2003)
Objective To evaluate the growth of low birth weight infants fedby fortified human milk (FHM) compared to human milk (HM) alone.Methods Sixty premature infants enrolled in this study and ran-domly assigned to have FHM and HM delivered by infusofeedpump,in parallel, non-blinded controlled trial. All patients were followeduntil day 30 or until discharge, whichever came first. The weightgain was recorded daily, while length and head circumference in-crement were recorded weekly.Results The FHM group gained more weight than the HM group(335.0+55.5 g vs. 290.6+108.4 g, p=0.000, 95%CI -170.2;-81.2),larger length increment (1.9+1.1cm vs. 1.2+0.4cm, p=0.000, 95%CI-1.37;-0.55), and larger head increment (1.87+1.1cm vs.0.91+0.43cm, 95%CI -1.37;-0.55). A similar result was found whenthe group was divided into subgroup of 1000-1499 g and 1500-1999 g birth weight. The larger calorie intake in the FHM groupwas the reason for better growth. No adverse effect related to theintervention was found.Conclusion The study shows the benefit of FHM in growth of lowbirth weight infants, which is consistent when the group is dividedinto 1000-1499 g birth weight and 1500-1999 g birth weight subgroups. Better growth is achieved through higher calorie intake inthe FHM group. No adverse effect is found as a consequence ofintervention